1990
DOI: 10.1128/jb.172.4.2113-2123.1990
|View full text |Cite
|
Sign up to set email alerts
|

A Caulobacter gene involved in polar morphogenesis

Abstract: At specific times in the cell cycle, the bacterium Caulobacter crescentus assembles two major polar organelles, the flagellum and the stalk. Previous studies have shown that flbT mutants overproduce flagellins and are unable to form chemotaxis swarm rings. In this paper, we report alterations in both the stalk and the flagellar structure that result from a mutation in the flagellar geneflbT. Mutant strains produce some stalks that have a flagellum, produce some stalks that have an extra lobe protruding from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

1990
1990
2001
2001

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…Electron micrographs revealed that the long cells were most often continuous and noncompartmentalized. Another morphological feature of flaS mutant strains was the presence of bifurcated stalks (>25% of the cells in the culture) similar to those seen with flbT mutants (15). In contrast, wild-type C. crescentus rarely (<1%) produces long, undivided cells (Fig.…”
Section: Resultsmentioning
confidence: 66%
See 2 more Smart Citations
“…Electron micrographs revealed that the long cells were most often continuous and noncompartmentalized. Another morphological feature of flaS mutant strains was the presence of bifurcated stalks (>25% of the cells in the culture) similar to those seen with flbT mutants (15). In contrast, wild-type C. crescentus rarely (<1%) produces long, undivided cells (Fig.…”
Section: Resultsmentioning
confidence: 66%
“…In contrast, wild-type C. crescentus rarely (<1%) produces long, undivided cells (Fig. 2B), and the occurrence of forked stalks was found to be approximately 1 to 5% (15).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The polar organelle has not been identified in all polarly flagellated bacteria, although it is possible that more subtle structures take on a similar role. For example, in C. crescentus, 10-nm-diameter polar particles of unknown function have been observed at the flagellated pole of predivisional cells and occasionally observed in the tips of stalks which are derived from a flagellated pole (18). Nonflagellated cells do not have any polar particles at the cell end.…”
Section: Morphological Differences At Cell Endsmentioning
confidence: 99%
“…Large (90 to 130 nm) disks associated with the outer membrane are another structural component of flagella found thus far only in polarly flagellated bacteria (12,18,22,42,55). These disks might serve to anchor the basal flagellar apparatus or to position the polar flagella (18).…”
Section: Methodsmentioning
confidence: 99%